Application of the Divisia Index with Interconnected Factors in the Warsaw Stock Exchange Index (WIG) fluctuation analysis - Białek, Jacek; Pietrzyk, Radosław (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
This paper presents a method of economic factorial analysis based on the Divisia index extended to interconnected factors. We verify the applicability of the presented method to financial market research by examining fluctuations of the Warsaw Stock Exchange WIG Index (WIG). We consider four main factors of WIG changes: the GDP growth, the PLN/EUR rate, the S&P500 and the unemployment rate. Due to computational reasons we apply the transformation that produces variables in the bigger the better form. We use quarterly data from the time interval between 2003 and 2014 divided into periods of bull and bear market. All considered variables are assumed to change linearly between quarters. The main conclusion is that during market prosperity, GDP and S&P500 changes exhibit the strongest influence on WIG changes.